Perplexing Jurisdiction Ratione Personae And Materiae of Rwandan Commercial Courts: Trader and Commercial Activity - Joel Niyobuhungiro (Yuridika, 2018)
Modernization of judiciary has prompted the reform of courts system in many countries whereby a trend of creating specialized courts is no doubt contributing to the needed justice. The creation of commercial courts, as specialized courts, has been and still is at the root of commercial development that contributes to economic growth of the country.Like any court, for commercial court to adjudicate case, a number of elements determining the court competence must be examined by the court seized. Jurisdiction ratione materiae and jurisdiction personae, inter alia, are the determining factors of the competence of commercial courts.  However, it can be difficult, in some cases, to ascertain court competence in case the law establishing those courts has not clearly delineated for example matters over which courts shall have jurisdiction. In Rwanda, The Law n° 06/2012/OL of 14/09/2012 determining the organization, functioning and jurisdiction of commercial courts, which repealed the Law n° 59/2007 of 16/12/2007, neither does it define a commercial activity nor does it define a trader. This creates big perplexity in determining commercial courts competence insofar as jurisdiction ratione materiae and personae are concerned. Commercial activities are neither defined nor enumerated in Rwanda laws. Rwandan commercial courts judges have tried to unravel that perplexity and tried to solve this problem in their judgements. However, it will be submitted that challenges posed by lack of clear definition of trader and commercial activity or at least a list of   commercial activities, calls for a clear stand of the legislator as far as jurisdiction ratione materiae and personae of Rwandan commercial courts are concerned.